2011
DOI: 10.3109/13693786.2010.502190
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatusbiofilms in the clinical setting

Abstract: We discuss in this work the role of Aspergillus biofilms in the clinical setting by reviewing the most recent findings on this topic. Aspergillus fumigatus can produce in vitro an extracellular hydrophobic matrix with typical biofilm characteristics under all static conditions tested, i.e., agar media, polystyrene and bronchial epithelial cells. Under static conditions the mycelial growth is greater than in shaken, submerged conditions. The extracellular matrix (ECM) is composed of galactomannan, α-1,3-glucans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
87
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 16 publications
0
87
0
1
Order By: Relevance
“…Similar structures containing extracellular DNA have been reported in vitro and in vivo and have been identified as the extracellular matrix of fungi (1,37,42). ECMs have only been recently identified, and there is little information on their role in the pathogenesis of fungal infections.…”
Section: Discussionmentioning
confidence: 82%
“…Similar structures containing extracellular DNA have been reported in vitro and in vivo and have been identified as the extracellular matrix of fungi (1,37,42). ECMs have only been recently identified, and there is little information on their role in the pathogenesis of fungal infections.…”
Section: Discussionmentioning
confidence: 82%
“…This growth phenotype, which complies with the definition of a biofilm (10), may help A. fumigatus to colonize the host substratum and to resist phagocytic and antimicrobial attacks, mimicking the typical Candida albicans or bacterial biofilm (8,11). Recent observations have consistently shown that all antifungal drugs are significantly less effective when A. fumigatus is grown as a biofilm than when it is grown in the planktonic state (4,7,9,12,13), presumably as a reflection of multiple resistance mechanisms, including the ECM, which would prevent drug diffusion by acting as a physical barrier (14). This could contribute to the overall mortality with invasive aspergillosis, which remains high, despite the use of newer broad-spectrum antifungal agents and diagnostic adjuncts (15).…”
mentioning
confidence: 99%
“…S imilar to biofilm-forming bacteria or yeasts (1), Aspergillus fumigatus, the most prevalent airborne fungal pathogen (2), is now largely acknowledged to be an organism able to grow and develop as a multicellular community (3), in which the hyphae are cohesively bonded together by a hydrophobic extracellular matrix (ECM) (4), under the aerial and static conditions found by the fungus either in vitro or in vivo (5)(6)(7)(8)(9). This growth phenotype, which complies with the definition of a biofilm (10), may help A. fumigatus to colonize the host substratum and to resist phagocytic and antimicrobial attacks, mimicking the typical Candida albicans or bacterial biofilm (8,11).…”
mentioning
confidence: 99%
“…Bien que des centaines de conidies soient inhalées chaque jour, les cas de pathologies sont rares car le système immunitaire de l'hôte est capable d'éliminer le champignon. Néanmoins, en cas d'altération du système immunitaire ou d'existence de pathologie pulmonaire sous-jacente (séquelle de tuberculose par exemple), il peut être responsable de pathologies graves, certaines pouvant potentiellement être mortelles [67]. Des données récentes montrent qu'A.…”
Section: Les Biofilms Fongiquesunclassified